Between Law and Development: The Effectiveness of the Law on the Capital City of the Nation - Hafizal Amin (CV. FOUNDAE, 2025)
The Law No. 3 of 2022 on the Capital City (UU IKN), as a legal representation in national development, is perceived to have questionable effectiveness. The procedural approach in its formation tends to neglect scientific considerations and accommodates oligarchic interests, thereby creating a public trust crisis regarding the role of law in development. This article aims to analyze the effectiveness of the UU IKN and assess to what extent this law reflects the interests of the public. This research employs a normative method with a library research approach, examining primary, secondary, and tertiary legal materials. The findings indicate that the UU IKN was not entirely drafted based on a comprehensive academic study, as there is a selective tendency to cite development theories that support the government's agenda. Furthermore, the implementation of UU IKN demonstrates the dominance of political interests, while the public faces negative impacts such as deforestation, evictions, and a lack of realization of development promises. Therefore, the effectiveness of law in the context of the IKN development remains a fundamental issue that requires critical review.